Baseline resting heart rate variability predicts post‐traumatic stress disorder treatment outcomes in adults with co‐occurring substance use disorders and post‐traumatic stress. (10th April 2019) - Soder, Heather E.; Wardle, Margaret C.; Schmitz, Joy M.; Lane, Scott D.; Green, Charles; Vujanovic, Anka A.
Abstract: Post‐traumatic stress disorder (PTSD) symptoms are highly prevalent among individuals with substance use disorders (SUD), presenting a difficult‐to‐treat, complex comorbidity. Prognostic factors for treatment outcomes may characterize heterogeneity of the treated population and/or implicate mechanisms of action that are salient for improving treatments. High frequency heart rate variability (HF‐HRV) is a suggested biomarker for emotion regulation—the ability to generate appropriate emotional responses via the influence of the parasympathetic nervous system on the heart. This initial study investigated the utility of baseline resting HF‐HRV for predicting PTSD symptoms and substance use outcomes following treatment of 37 SUD participants with comorbid PTSD symptoms. Participants completed either standard cognitive‐ behavioral therapy (CBT) for SUD or a novel treatment of integrated post‐traumatic stress and substance use that combined CBT for SUD with cognitive processing therapy for PTSD. Analyses demonstrated that higher HF‐HRV predicted greater reduction in PTSD symptoms following both types of treatment. This suggests prognostic value of HF‐HRV as a predictor of PTSD treatment outcomes; those with poorer autonomic emotional regulation may not respond as well to psychotherapy in general. This hypothesis‐generating analysis identifies a putative biomarker that might have utility in treatment prediction. Abstract : Trauma exposure is reported in 90% of individuals with substance use disorders (SUDs), with 30%–50% meeting full criteria for post‐traumatic stress disorder (PTSD). Those with comorbid SUD and PTSD have worse treatment outcomes, emphasizing the need for more research identifying potential mechanisms of poor treatment outcomes. High‐frequency heart rate variability is a potential biomarker of emotion regulation, a process that has been implicated in both SUD and PTSD treatment. The current study is the first to investigate heart rate variability as a prognostic biomarker of treatment outcomes for this difficult‐to‐treat population.